2014
DOI: 10.1002/ijop.12131
|View full text |Cite
|
Sign up to set email alerts
|

The curvilinear effect of work engagement on employees' turnover intentions

Abstract: Numerous studies have shown the positive consequences of work engagement for both organisations and employees experiencing it. For instance, research has demonstrated that work-engaged employees have lower levels of turnover intentions than non-engaged employees. However, in this research, we examined whether there is a dark side of work engagement. More precisely, we investigated whether the relationship between work engagement and employees' turnover intentions might be non-linear. Based on two different sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
69
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(88 citation statements)
references
References 25 publications
11
69
0
1
Order By: Relevance
“…3) Absorption is "the state in which one is fully concentrated in his/her work; employees feel that time flies when working and have difficulties with detaching from working." In reference to Caesens, Stinglhamber & Marmier (2016) [14], it states that if an organization provides valued resources to employees, it would foster the motivational process and the result would be that employees would be less inclined to leave their organization (Schaufeli & Bakker, 2004 [15]). …”
Section: Introductionmentioning
confidence: 99%
“…3) Absorption is "the state in which one is fully concentrated in his/her work; employees feel that time flies when working and have difficulties with detaching from working." In reference to Caesens, Stinglhamber & Marmier (2016) [14], it states that if an organization provides valued resources to employees, it would foster the motivational process and the result would be that employees would be less inclined to leave their organization (Schaufeli & Bakker, 2004 [15]). …”
Section: Introductionmentioning
confidence: 99%
“…The existing literature defining the causes of PCF in the workplace (Rodwell, Ellershaw, & Flower, 2015) and the reasons for the high rate of voluntary employee turnover (Memon, Salleh, & Baharom, 2016) has been insufficient. Study results were consistent with the findings of Caesens et al (2016) and of Kasekende (2017), although their studies were not based exclusively on healthcare employee perceptions. No other studies were identified which evaluated the influence of PCF on employee engagement and turnover intention outcomes in a healthcare setting.…”
Section: Theoretical Implications Of Studysupporting
confidence: 91%
“…High-performance organizations provide professional development for their employees to drive motivation and enhance skills (Ma & Chang, 2013). Adopting HRM practices that foster employee engagement has been beneficial to organizations (Caesens, Stinglhamber, & Marmier, 2016). Best-in-class employers must be proactive in benchmarking and communicating their practices so that employees perceive them as differentiators as opposed to what competitors offer (Gardner et al, 2015).…”
Section: Hrm Practices and Organizational Performancementioning
confidence: 99%
See 2 more Smart Citations